The spatial architecture of neuroimmune interactions in epilepsy - Chu, Dianwu; Zhang, Wuhao; Zhou, Xing; Yin, Hang; Yin, Jian (Frontiers in Immunology, 2026)
Epilepsy is increasingly recognized as a disorder not only of neuronal dysfunction but also of immune dysregulation within the central nervous system (CNS). Accumulating evidence points to a critical role for the immune microenvironment in shaping epileptogenesis—the process that underlies the development and progression of epilepsy. In this Review, we examine the spatial dynamics of neuroimmune interactions, highlighting how local inflammatory niches emerge and evolve across brain compartments such as the parenchyma and perivascular space. We describe how the spatial organization and activation of resident glial cells, alongside the infiltration of peripheral immune cells facilitated by blood–brain barrier (BBB) disruption, contribute to region-specific patterns of neuroinflammation. Critically, we emphasize that understanding “where” these neuroimmune interactions occur—their precise spatial organization within distinct cellular microenvironments—is as fundamental as identifying “what” immune cells are involved or “how” they function. Particular focus is given to the localized actions of immune mediators, including regulatory T cells and pro-inflammatory cytokines such as IL-1β, IL-6, and TNF-α, and their influence on neuronal excitability. We also discuss the spatiotemporal heterogeneity of immune signatures across different epilepsy syndromes, drawing from both experimental models and clinical observations. Finally, we explore emerging therapeutic strategies that target spatially defined immune responses and consider the potential of spatial biomarkers and advanced tissue-mapping technologies to refine disease classification and guide precision therapies. By positioning the spatial immune landscape as a central feature of epileptogenesis, we propose a framework for developing effective, potentially curative interventions for epilepsy.